Traceless enzymatic synthesis of monodispersed hypermodified oligodeoxyribonucleotide polymers from RNA templates - Ondruš, Marek; Sýkorová, Veronika; Hocek, Michal (Chemical communications (Cambridge, England), 2022)
We have developed a new alternative for enzymatic synthesis of single-stranded hypermodified oligodeoxyribonucleotides displaying four different hydrophobic groups based on reverse transcription from RNA templates catalyzed by DNA polymerases using a set of base-modified dNTPs followed by digestion of RNA by RNases. Using mixed oligodeoxyribonucleotide primers containing a ribonucleotide at the 3'-end, RNase AT1 simultaneously digested the template and cleaved off the primer to release a fully modified oligonucleotide that can be further 3'-labelled with a fluorescent nucleotide using TdT. The resulting hypermodified oligonucleotides could find applications in selection of aptamers or other functional macromolecules.
Keywords: DNA primery; Polymers; genetické matrice; DNA-Directed DNA Polymerase; Oligonucleotides; RNA; Oligodeoxyribonucleotides; Ribonucleases; Templates, Genetic; DNA Primers; polymery; ribonukleasy; oligodeoxyribonukleotidy; ribonukleotidy; oligonukleotidy; Ribonucleotides; DNA-dependentní DNA-polymerasy